Actividades rectoras (juego y exploración del medio) orientadas al fortalecimiento del enfoque educativo ambiental en preescolar (2019)
This research focuses on the leading activities introduced at the preschool level of educational institutions and how teachers apply them for the development of the strengthening of the environmental dimension in curricular preschool plans. The objective is to design a proposal of a didactic - technological nature that, based on the integration of the governing activities (exploration of the environment and the game) into the preschool curriculum, contributes to the strengthening of the environmental educational approach. For this, an inductive methodological route is designed that works through a documentary and field design, which allows the execution of a questionnaire in certain preschool teachers of several educational institutions. It is recognized that there are teachers who appropriate the curricular activities and projects that take into account the governing activities and that in some cases it can be determined that their use in the classrooms is carried out, but a large number of teachers what they do this kind of activities. With this, it is concluded that the Governing Activities help and support the creation of strategies that allow the strengthening of the environmental education approach with that of leading to high-quality teaching-learning processes. Given this situation, a proposal is developed that involves an interactive virtual platform, a booklet that informs and directs the environmental fundamentals and finally a children's round that appropriates the concepts already seen.